Xenopus Cds1 Is Regulated by DNA-Dependent Protein Kinase and ATR during the Cell Cycle Checkpoint Response to Double-Stranded DNA Ends - McSherry, Troy D. (Mol Cell Biol, 2004)
The checkpoint kinase Cds1 (Chk2) plays a key role in cell cycle checkpoint responses with functions in cell cycle arrest, DNA repair, and induction of apoptosis. Proper regulation of Cds1 is essential for appropriate cellular responses to checkpoint-inducing insults. While the kinase ATM has been shown to be important in the regulation of human Cds1 (hCds1), here we report that the kinases ATR and DNA-dependent protein kinase (DNA-PK) play more significant roles in the regulation of Xenopus Cds1 (XCds1). Under normal cell cycle conditions, nonactivated XCds1 constitutively associates with a Xenopus ATR complex. The association of XCds1 with this complex does not require a functional forkhead activation domain but does require a putative SH3 binding region that is found in XCds1. In response to double-stranded DNA ends, the amino terminus of XCds1 is rapidly phosphorylated in a sequential pattern. First DNA-PK phosphorylates serine 39, a site not previously recognized as important in Cds1 regulation. Xenopus ATM, ATR, and/or DNA-PK then phosphorylate three consensus serine/glutamine sites. Together, these phosphorylations have the dual function of inducing dissociation from the ATR complex and independently promoting the full activation of XCds1. Thus, the checkpoint-mediated activation of XCds1 requires phosphorylation by multiple phosphoinositide 3-kinase-related kinases, protein-protein dissociation, and autophosphorylation.